Synthesis and Characterizations of Hollow Spheres of Platinum Nanoparticles Using Se@Pt as Precursor - Yang, Ming; Xia, Juanjuan; Huang, Yu (Asian Journal of Chemistry, 2015)
Hollow spheres of platinum nanoparticles with an average diameter of 50-200 nm have been prepared by spheres of Se@Pt reaction with aqueous hydrazine. The products were characterized by X-ray powder diffraction, transmission electron microscopy, X-ray photoelectron spectra and and UV-visible absorption spectroscopy. The sizes of the nanoparticles of platinum were estimated by Debye-Scherrer formula according to XRD spectrum.